Video analysis of situations with a high-risk for injury in Norwegian male professional football; a comparison between 2000 and 2010. Issue 9 (11th January 2013) - Bjørneboe, John; Bahr, Roald; Einar Andersen, Thor
Abstract : Background: A recent study from Norwegian male professional football found that the risk of acute match injuries increased from 2002 to 2007. Objective: To compare the incidence of incidents with a propensity for injury, from the 2000 season to the 2010 season in Norwegian male professional football using video analysis. Methods: We conducted a video analysis of incidents in Norwegian professional football. An incident was recorded if the match was interrupted by the referee, and the player lay down for more than 15 s, and appeared to be in pain or received medical treatment. We also conducted a video analysis of all player-to-player contact situations occurring during 30 randomly selected matches. Results: A total of 1287 incidents were identified during the two seasons. The corresponding rate of incidents was 74.4 (95% CI 67.3 to 81.5) in the 2000 season and 109.6 (95% CI 102.3 to 116.9) in the 2010 season, a significant increase from 2000 to 2010 (rate ratio 1.47, 95% CI 1.31 to 1.66). We observed a significantly higher rate of opponent-to-player contact and non-contact incidents in the 2010 season, but no change in the proportion of fouls or sanctions awarded by the referee. The rate of player-to-player contact situations in both heading and tackling duels was lower during the 2010 season. Conclusions: We found an increased rate of non-contact and opponent-to-player contact incidents in both heading and tackling duels in the 2010 season compared with 10 years earlier, even if there was no increase in the frequency of player-to-player contact situations.